A flexible framework for distributed shared objects - Weber, Stefan (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2002)
A distributed shared memory (DSM) system ensures the consistency of shared data in a distributed system while providing the programming paradigm of a single-processor system. Recent DSM systems provide increasingly more support for the sharing of objects rather than portions of memory. However, like earlier DSM systems these distributed shared object (DSO) systems still rely upon a single protocol, or a small set of given protocols, for the sharing of application objects. This limitation prevents the applications from optimizing the underlying communication behaviour on a per-application basis
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin